Teacher’s Elicitation Techniques in Teaching Expressing Agreement for 8th Grade Students at UPT SMP Negeri 17 Medan - D. Trisha Laxmi; Ariatna (Universitas Negeri Medan, 2025)
This study investigates the types of elicitation techniques used by an English teacher and how these techniques were implemented in teaching expressions of agreement to Grade 8 students at UPT SMP Negeri 17 Medan. Utilizing a qualitative descriptive design, data were obtained through classroom observations and teacher interviews. The findings indicate that the teacher applied five types of elicitation techniques as proposed by Doff (2013): asking questions, using pictures, texts/dialogues, games/activities, and non-verbal language. Among these, direct questioning and text/dialogue-based elicitation frequently, were mostly employed. These techniques were implemented systematically across the pre-teaching, whilst-teaching, and post-teaching stages to promote student participation, enhance interaction, and support comprehension. The study underscores the significance of varied elicitation techniques in fostering student-centered learning and improving students’ communicative competence.